АЙДОС БИЙ КИМ БОЛҒАН, ЯМАСА ХАЛЫҚ АҢЫЗ ӘПСАНАЛАРЫНЫҢ ТАРИЙХЫЙ ШЫНЛЫҚҚА ҚАТНАСЫ МӘСЕЛЕСИ ҲАҚҚЫНДА ГЕЙПАРА ОЙЛАР - Пазылов, М. (SCIENCE and SOCIETY, 2019)
The article deals with the analysis of contradicting ideas about Aydos biy based on some written recourses.
Keywords: spirit; valuable; idol (model); innocent; priceless; inheritance; legend; wish; biy (head of the tribe); sufferer; solemnity; reciprocal respect